Recurrent rhabdomyolysis in a collegiate athlete: A case report - Krivickas, L. S. (Medicine & Science in Sports & Exercise, 2006)
Purpose: Hereditary metabolic disorders can cause rhabdomyolysis in athletes. Team physicians should be aware of the presentation, workup, and management of the most common of these disorders, carnitine palmitoyltransferase (CPT) II deficiency and muscle phosphorylase deficiency.